Analysis of the Influence of Korean Popular Culture on the Impact of A K-Popers' Appetite - Herdany Venny; Irawan Diki (Faculty of Social and Political Science Universitas Maritim Raja Ali Haji, Indonesia, 2023)
K-Lovers is a term used to describe Korean fans who are enthusiastic about everything related to K-pop singers, from news and albums to concerts and Korean TV shows featuring K-pop singers. Additionally, since becoming interested in K-pop culture, they have developed a taste for Korean fashion, food, music, and movies. The purpose of this study is to explore (1) how people first became interested in K-pop and developed a liking for it, (2) changes in their preferences for fashion, food, music, and movies (dramas), and (3) the positive and negative impacts of liking K-pop. The research method used in this study is qualitative with a descriptive approach. The results of the study indicate that the informants became interested in K-pop through social media, particularly Facebook. After becoming fans of K-pop, their preferences for fashion, food, music, and movies (dramas) changed. The positive impact of liking K-pop was increased self-confidence and reduced sensitivity to others' opinions. The negative impact was experiencing bullying.